2021
DOI: 10.2147/dmso.s317417
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Preserves Pancreatic Islets Structure Through Upregulation of Pancreatic β-Catenin in Hypothyroid Rats

Abstract: Background Altered status of thyroid hormones, which have a key role in regulating metabolism, was reported to affect glucose homeostasis and insulin secretion. Objective This study was designed to assess the impact of propylthiouracil (PTU)-induced hypothyroidism on the pancreatic islet cells and the efficacy of thymoquinone (TQ) in alleviating this impact and explore the mechanism behind it alleviating oxidative stress and affecting β-catenin expression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The statistical analysis revealed a considerable drop in the serum T3 and T4 concentrations; also, the TSH showed a significant rise in comparison to the control values. The current findings were in agreement with a number of studies (26,30). The theory underlying the PTU action mechanism is based on the fact that the thyroid peroxidase enzyme regulates T4 production, which in turn restricts thyroid hormone release and the conversion of T3 and T4 into their active forms in peripheral tissues (31 and 32).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The statistical analysis revealed a considerable drop in the serum T3 and T4 concentrations; also, the TSH showed a significant rise in comparison to the control values. The current findings were in agreement with a number of studies (26,30). The theory underlying the PTU action mechanism is based on the fact that the thyroid peroxidase enzyme regulates T4 production, which in turn restricts thyroid hormone release and the conversion of T3 and T4 into their active forms in peripheral tissues (31 and 32).…”
Section: Discussionsupporting
confidence: 91%
“…Rats in the PTU-group were given 6 mg/kg/day of (26) propylthiouracil orally. Rats in PTU+Ash group received oral doses of both propylthiouracil (6 mg/kg/day) (26) and ashwagandha extract (Ash) (50 mg/kg/day) (27). For a total of 30 days, the therapies were administered orally while using a gastric tube.…”
Section: Experimental Designmentioning
confidence: 99%
“…In the present work, the hypothyroid status was achieved by administration of propylthiouracil (PTU) for 6 weeks and its establishment was con rmed by a decrease in serum level of T3 and T4 and an increase in TSH level (Faddladdeen et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, PTU was used to induce hypothyroidism in rats, which was serologically monitored. This drug was used in previous studies to induce an animal model of hypothyroidism (23) . It was reported that PTU blocks the production of newly secreted thyroid hormone in the thyroid gland.…”
Section: Discussionmentioning
confidence: 99%